The bioartificial thyroid: a biotechnological perspective in endocrine organ engineering for transplantation replacement - Toni, Roberto; Della Casa, Claudia; Spaletta, Giulia; Marchetti, Giacomo; Mazzoni, Perseo; Bodria, Monica; Ravera, Simone; Dallatana, Davide; Castorina, Sergio; Riccioli, Vincenzo; Castorina, Emilio Giovanni; Antoci, Salvatore; et al. (Acta Biomedica Atenei Parmensis, 2007)
A new concept for ex situ endocrine organ bioengineering is presented, focused on the realization of a human bioartificial thyroid gland. It is based on the theoretical assumption and experimental evidence that symmetries in geometrical coordinates of the thyroid tissue remain invariant with respect to developmental, physiological or pathophysiological transformations occuring in the gland architecture. This topological arrangement is dependent upon physical connections established between cells, cell adhesion molecules and extracellular matrix, leading to the view that the thyroid parenchyma behaves like a deformable “putty”, moulded onto an elastic stromal/vascular scaffold (SVS) dictating the final morphology of the gland. In particular, we have raised the idea that the geometry of the SVS per se provides pivotal epigenetic information to address the genetically-programmed, thyrocyte and endothelial/vascular proliferation and differentiation towards a functionally mature gland, making organ form a pre-requirement for organ function. A number of experimental approaches are explored to obtain a reliable replica of a human thyroid SVS, and an informatic simulation is designed based on fractal growth of the thyroid intraparenchymal arterial tree. Various tissue-compatible and degradable synthetic or biomimetic polymers are discussed to act as a template of the thyroid SVS, onto which to co-seed autologous human thyrocyte (TPC) and endothelial/vascular (EVPC) progenitor cells. Harvest and expansion of both TPC and EVPC in primary culture are considered, with specific attention to the selection of normal thyrocytes growing at a satisfactory rate to colonize the synthetic matrix. In addition, both in vitro and in vivo techniques to authenticate TPC and EVPC lineage differentiation are reviewed, including immunocytochemistry, reverse trascriptase-polymerase chain reaction, flow cytomery and proteomics. Finally, analysis of viability of the thyroid construct following implantation in animal hosts is proposed, with the intent to obtain a bioartificial thyroid gland morphologically and functionally adequate for transplantation. We believe that the biotechnological scenario proposed herein may provide a template to construct other, more complex and clinically-relevant bioartificial endocrine organs ex situ, such as human pancreatic islets and the liver, and perhaps a new approach to brain bioengineering.